Stability of a Mixed‐Valence Hydrous Iron‐Rich Oxide: Implications for Water Storage and Dynamics in the Deep Lower Mantle. Issue 5 (21st May 2022) - Liu, Lu; Yang, Ziqiang; Yuan, Hongsheng; Meng, Yue; Giordano, Nico; Sun, Junliang; Du, Xueyan; Dalladay‐Simpson, Philip; Wang, Junyue; Zhang, Li
Abstract: Incorporation of water into mantle compositions can have significant effects on the phase relations in the systems. In this study, we synthesized an iron‐rich hexagonal hydrous phase (referred to as "HH1‐phase") under the high pressure‐temperature ( P ‐ T ) conditions of the deep lower mantle and determined the crystal structure of the HH1‐phase at 79 GPa using the multigrain crystallography method. The chemical formula obtained was Fe12.76 O18 H x ( x ∼ 4.5) in the Fe‐O‐H system. To demonstrate the role of HH1‐phase for water storage in multicomponent systems relevant to mantle compositions, we investigated the stability of HH1‐phase in both MgO‐rich pyrolitic and SiO2 ‐rich basaltic compositions. Our results indicate that the HH1‐phase serves as major water storage in a pyrolitic composition, whereas the Al‐rich CaCl2 ‐type δ‐phase and SiO2 phase are major water storage phases in a SiO2 ‐rich basaltic composition. Incorporation of considerable amounts of SiO2, MgO, and Al2 O3 into the HH1‐phase expands its stability field from 98 GPa in the Fe‐Al‐O‐H system to at least 108 GPa (corresponding to ∼2, 400 km depth) in the Mg‐Si‐Al‐Fe‐O‐H system. Plumes of hot upwelling rock rooted at the base of the lower mantle have been proposed as a possible origin of hotspot volcanoes. The hydrous Fe‐rich HH1‐phase, if included into the material of upwelling plumes, will decompose on its rising to the upper part of the lower mantle and release water. Our results should provide constraints on water storage in the deep lower mantle and have implications for deep mantle dynamics. Plain Language Summary: Incorporation of water into mantle compositions can have significant effects on the phase relations in the system. In this study, we conducted experiments under high pressure‐temperature ( P ‐ T ) conditions of the deep lower mantle in a laser‐heated diamond anvil cell. We synthesized an iron‐rich hexagonal hydrous phase (referred to as "HH1‐phase") as Fe12.76 O18 H x ( x ∼ 4.5) in the Fe‐O‐H system and confirmed the stability of HH1‐phase in multicomponent mantle systems under high P‐T conditions corresponding to the depth of 1, 900–2, 400 km. Our results indicate that the HH1‐phase could play a major role as water storage in a pyrolitic deep lower mantle. Plumes of hot upwelling rock rooted at the base of the lower mantle have been proposed as a possible origin of hotspot volcanoes. The hydrous Fe‐rich HH1‐phase, if included into the material of upwelling plumes, will decompose on its rising to the upper part of the lower mantle and release water. Our results should provide constraints on water storage in the deep lower mantle and have implications for deep mantle dynamics. Key Points: An iron‐rich hexagonal hydrous phase is stable at 1, 900–2, 400 km depth Chemical composition of the hydrous phase was found to vary with bulk composition and with pressure The iron‐rich hydrous phase could be major water storage in a pyrolitic deep lower mantle and decompose in upwelling plumes